[OP.LB01.11] MEASUREMENT OF ANGIOTENSIN II AT EQUILIBRIUM IN THE DIAGNOSTIC WORKUP OF PRIMARY ALDOSTERONISM. IMPACT OF PATIENT POSITIONING AND ACE INHIBITOR TREATMENT. (September 2016) - Poglitsch, M.; Ahmed, A.H.; Stoller, A.; Van Oyen, D.; Schwager, C.; Aigner, C.; Domenig, O.; Haschke, M.; Stowasser, M.
Abstract : Objective: Primary aldosteronism (PA) is a widely under-diagnosed, potentially curable and specifically treatable cause of hypertension. PA screening involves measuring the aldosterone-to-renin-ratio (ARR), but false negative results can occur in the setting of medications, which block the renin-angiotensin system (RAS). Withdrawing RAS blockers from patients with resistant hypertension is not without cardiovascular risk. A novel diagnostic approach, the aldosterone-to-angiotensin-II-ratio (AA2-Ratio), has the potential for less drug interference and improved reliability in PA screening and confirmation of diagnosis. Design and method: Serum samples from 80 patients undergoing PA confirmation testing were analyzed. Sampling was performed in a recumbent (7 a.m.) and in an upright (10 a.m.) position before and after 4 days of oral administration of fludrocortisone and salt loading. The concentrations of renin, aldosterone and equilibrium Angiotensin-II were determined and ARR and AA2-Ratios were calculated. The interference of ACE-inhibition with the AA2-Ratio was investigated in healthy volunteers receiving 10 mg enalapril daily for 8 days. Results: Renin concentration was undetectable in more than 40% of samples, while equilibrium Angiotensin-II was measurable in 98% of all 320 samples analyzed. Angiotensin-II levels were significantly higher in upright collected samples compared to samples collected in a recumbent position. Comparison of the ARR with the AA2-Ratio revealed a significantly larger diagnostic window for the AA2-Ratio. While the ARR was significantly suppressed by ACE-inhibitor treatment, the AA2-Ratio remained unaffected by ACE-inhibition. Conclusions: The AA2-Ratio may be superior to the ARR in PA screening among hypertensive patients. Equilibrium Angiotensin-II levels show expected responses to posture and appear to outperform renin concentration as a marker for RAS activation in terms of sensitivity, giving a measurable readout even in clinical states characterized by markedly suppressed RAS activity. The stability of the AA2-Ratio in the presence of ACE-inhibition points to a potential use of the AA2-Ratio PA screening in hypertensive patients without ACE-inhibitor discontinuation.